2002
DOI: 10.1038/sj.bjc.6600266
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant androgen deprivation impacts late rectal toxicity after conformal radiotherapy of prostate carcinoma

Abstract: To evaluate whether androgen deprivation impacts late rectal toxicity in patients with localised prostate carcinoma treated with three-dimensional conformal radiotherapy. One hundred and eighty-two consecutive patients treated with 3DCRT between 1995 and 1999 at our Institution and with at least 12 months follow-up were analysed. three-dimensional conformal radiotherapy consisted in 70 -76 Gy delivered with a conformal 3-field arrangement to the prostate+seminal vesicles. As part of treatment, 117 patients (64… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…(5,6) Other authors have also suggested a relationship between RT, GI toxicity and androgen deprivation. (7,8) The purpose of this study is to evaluate the incidence of long term treatment sequelae grade 3 or higher (grade 3+) in patients treated on RTOG studies 85-31, 86-10 and 92-02, looking to evaluate any changes in late toxicity incidence with specific evaluation of the potential effect of hormone therapy on late GI, GU, and other sequelae in patients receiving definitive radiation therapy for adenocarcinoma of the prostate.…”
Section: Introductionmentioning
confidence: 99%
“…(5,6) Other authors have also suggested a relationship between RT, GI toxicity and androgen deprivation. (7,8) The purpose of this study is to evaluate the incidence of long term treatment sequelae grade 3 or higher (grade 3+) in patients treated on RTOG studies 85-31, 86-10 and 92-02, looking to evaluate any changes in late toxicity incidence with specific evaluation of the potential effect of hormone therapy on late GI, GU, and other sequelae in patients receiving definitive radiation therapy for adenocarcinoma of the prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Others have hypothesized that the adjuvant hormones slow the reparative process of the irradiated rectum, thereby increasing the susceptibility to develop a late rectal injury. 18 We reduced the utility of patients experiencing rectal toxicity in our model, and LTAD still was found to be cost-effective, even when the utility of the hormone therapy was decreased to 0.6. We did not include the potential for increased cost for the treatment or prevention of osteoporosis in patients who received LTAD.…”
Section: Discussionmentioning
confidence: 99%
“…3 Increased late toxicity in patients who received androgen deprivation for the treatment of prostate carcinoma also was reported by others. 17,18 The increases in toxicity and cost must be counterbalanced by an increase in incremental qualityadjusted survival. An incremental increase in qualityadjusted survival does occur to justify the increase in cost and toxicity experienced by patients who receive LTAD.…”
Section: Discussionmentioning
confidence: 99%
“…33 This potential for reducing toxicity is countered, however, by (a) the potential for reducing normal tissue tolerance and (b) if RT planning is done while the HT is still causing continued cytoreduction, the possibility of the RT treatment fields being overly generous for the still-shrinking prostate. Indeed, some investigators have reported an increase in acute GU toxicity (a finding limited to those with poor baseline urinary function), 28 and an increase in late GI toxicity 31 with the addition of HT to RT. Using the smaller post-HT fields does carry the risk, however, of not reaching disease at the periphery of the pre-HT prostate.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of HT on acute and late RT toxicity has been the subject of several prior investigations. [28][29][30][31][32][33][34][35] One major theoretical advantage of neoadjuvant HT is the potential for cytoreduction of the prostate to reduce the overlap of the treatment volume with the surrounding bladder and rectum-indeed, several investigators have documented the potential role of cytoreduction in improving rectal and bladder dose volume histograms for EBRT 29,30,32,34 and in reducing the number of needles/ seeds for interstitial brachytherapy. 33 This potential for reducing toxicity is countered, however, by (a) the potential for reducing normal tissue tolerance and (b) if RT planning is done while the HT is still causing continued cytoreduction, the possibility of the RT treatment fields being overly generous for the still-shrinking prostate.…”
Section: Introductionmentioning
confidence: 99%